A peer-nomination assessment of electronic forms of aggression and victimization. (October 2015) - Badaly, Daryaneh; Duong, Mylien T.; Ross, Alexandra C.; Schwartz, David
Abstract: The perpetration and receipt of electronic aggression have largely been assessed with self-report questionnaires. Using a sample of 573 adolescents, the current study compared the psychometric properties of a peer-nomination measure of electronic aggression and victimization to the more widely used self-report approach. Estimates of the reliability, stability, and concordance of peer- and self-report assessments were adequate, mirroring those from research on aggressive exchanges in school. Analyses of validity and utility revealed that peer-nominations, compared to self-reports, provide overlapping and distinct information on adolescents' social, emotional, and academic adjustment. Overall, these findings provide evidence that peer-nominations are a reliable, valid, and useful means for measuring electronic aggression and victimization. Future work will benefit from their incorporation into multi-method assessments.